2007
DOI: 10.1108/02652320710772998
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the impact of a retailer's relationship efforts on customers' attitudes and behavioral intentions

Abstract: Purpose -The purpose of the paper is to summarize existing evidence about the behavioral sequence of relationship marketing at the individual customer level, and also to offer a conceptual model of the impact of particular behaviors that signal whether customers remain with or defect from the company. Design/methodology/approach -Based on the SEM tool of Lisrel (Linear Structure Relation), This study develops and empirically tests a model for examination of the impact of different relationship efforts (financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 91 publications
11
45
0
Order By: Relevance
“…Trust has been found to be a factor affecting commitment in many previous studies (Morgan and Hunt, 1994;Gannesan, 1994;Moorman, Zaltman and Desphande, 1992;Kassim and Abdulla, 2006;Liang and Wang, 2007).…”
Section: Trustmentioning
confidence: 92%
“…Trust has been found to be a factor affecting commitment in many previous studies (Morgan and Hunt, 1994;Gannesan, 1994;Moorman, Zaltman and Desphande, 1992;Kassim and Abdulla, 2006;Liang and Wang, 2007).…”
Section: Trustmentioning
confidence: 92%
“…Commitment has also been found to be significantly related to behaviour intention and, with respect to its different categories as proposed by Parasuraman et al (1994), to different service, retail and luxury brand contexts (Fullerton, 2014;Jani and Han, 2011;Liang and Wang, 2007;Moreira and Silva, 2015;Shukla, Banerjee and Singh, 2016). Therefore, two relationship quality factors -customer satisfaction and commitment -are hypothesised to have significant relationships with each other and the behavioural intention of customers when post-purchase service and repairs at a luxury motor vehicle dealership are considered.…”
Section: The Relationships Between Customer Satisfaction Commitment mentioning
confidence: 96%
“…The studies conducted in different service-, retail-and luxury brand-related contexts as well as online environments (Becerra and Korgoankar, 2011;Forgas-Coll, Palau-Saumell, Sánchez-García and Caplliure-Giner, 2014;Liang and Wang, 2007;Limbu, Wolf and Lunsford, 2012) bear testament to the fact that trust has a significant positive relationship with customers" behavioural intentions. It was also found that trust holds a significant relationship with commitment in various service-related contexts as well as in a luxury brand context (Moreira and Silva, 2015;Ou et al, 2011;Sumaedi, Juniarti and Bakti, 2015;Shukla et al, 2016).…”
Section: The Relationships Between Trust Commitment and Behavioural mentioning
confidence: 99%
“…Studies (Berry, 1983;Voss and Voss, 1997;Gwinner et al, 1998;Odekerken-Schroder et al, 2003;Liang and Wang, 2007;Dalziel et al, 2011) indicate that there is a positive association between marketer's RM strategies and customer's relationship satisfaction (CS).…”
Section: Introductionmentioning
confidence: 99%
“…Extant literature (e.g. Voss and Voss, 1997;Gwinner et al, 1998;Liang and Wang, 2007) shows that marketers/service providers widely use RM strategies such as personal communication, PT and rewarding to have long-term relationship with their customers. And these RM strategies contribute to the development of customer perception about the marketer's/ service provider's RM orientation.…”
Section: Introductionmentioning
confidence: 99%